Cost analysis of intracranial aneurysmal repair by endovascular coiling versus flow diversion: At what size should we use which method?. Issue 4 (20th February 2013) - Chiu, Albert H; Nadarajah, Mahen; Wenderoth, Jason D
Abstract: Introduction: Flow diverters enable intracranial aneurysmal repair without the need to enter the aneurysm sac. Concerns, however, have been raised regarding the cost compared with coiling techniques. The aim of this study was to evaluate the relative costs for different aneurysm sizes to ascertain if different sizes are more cost‐effectively treated by a particular method. Methods: Patients undergoing aneurysmal repair at two neurovascular referral centres between September 2005 and August 2010 were included; patients who underwent coiling for recurrences of prior microneurosurgical clipping were excluded. These aneurysms were stratified into three size groups. The average and median number of coils or flow diverters and the average and median costs of treatment of each size category were calculated. Results: Four hundred twenty‐nine aneurysms were treated. Of these, 409 were coiled with or without assist devices. Forty‐eight per cent fell under Group A (<7 mm), 36% under Group B (7–12 mm) and 16% under Group C (>12 mm). Twenty aneurysms were flow diverted. Of these, 14 were treated de novo, five previously coiled and one previously clipped. Twenty per cent belonged in Group A, 25% in Group B and 55% in Group C. The highest procedural costs in the coiling group were Group C aneurysms requiring stent assistance, with an average of $24 563 (median $23 860). Using flow diversion, the average was $24 650 (median $16 490). Conclusion: Given the price parity threshold crossed for aneurysms >12 mm requiring stent assistance and the relative ease of the flow diverter technique, we suggest that flow diversion should be considered the first‐line treatment for aneurysms in this category.